Effect of Temperature on Tolbutamide Binding to Glycated Serum Albumin - Szkudlarek, Agnieszka (Molecules, 2017)
Glycation process occurs in protein and becomes more pronounced in diabetes when an increased amount of reducing sugar is present in bloodstream. Glycation of protein may cause conformational changes resulting in the alterations of its binding properties even though they occur at a distance from the binding sites. The changes in protein properties could be related to several pathological consequences such as diabetic and nondiabetic cardiovascular diseases, cataract, renal dysfunction and Alzheimer’s disease. The experiment was designed to test the impact of glycation process on sulfonylurea drug tolbutamide-albumin binding under physiological (T = 309 K) and inflammatory (T = 311 K and T = 313 K) states using fluorescence and UV-VIS spectroscopies. It was found in fluorescence analysis experiments that the modification of serum albumin in tryptophanyl and tyrosyl residues environment may affect the tolbutamide (TB) binding to albumin in subdomain IIA and/or IIIA (Sudlow’s site I and/or II), and also in subdomains IB and IIB. We estimated the binding of tolbutamide to albumin described by a mixed nature of interaction (specific and nonspecific). The association constants [Formula: see text] (L∙mol(−1)) for tolbutamide at its high affinity sites on non-glycated albumin were in the range of 1.98–7.88 × 10(4) L∙mol(−1) (λ(ex) = 275 nm), 1.20–1.64 × 10(4) L∙mol(−1) (λ(ex) = 295 nm) and decreased to 1.24–0.42 × 10(4) L∙mol(−1) at λ(ex) = 275 nm (T = 309 K and T = 311 K) and increased to 2.79 × 10(4) L∙mol(−1) at λ(ex) = 275 nm (T = 313 K) and to 4.43–6.61 × 10(4) L∙mol(−1) at λ(ex) = 295 nm due to the glycation process. Temperature dependence suggests the important role of van der Waals forces and hydrogen bonding in hydrophobic interactions between tolbutamide and both glycated and non-glycated albumin. We concluded that the changes in the environment of TB binding of albumin in subdomain IIA and/or IIIA as well as in subdomains IB and IIB influence on therapeutic effect and therefore the studies of the binding of tolbutamide (in diabetes) to transporting protein under glycation that refers to the modification of a protein are of great importance in pharmacology and biochemistry. This information may lead to the development of more effective drug therapy in people with diabetes.